2006
DOI: 10.1007/s00420-005-0057-4
|View full text |Cite
|
Sign up to set email alerts
|

From chemosensory thresholds to whole body exposures—experimental approaches evaluating chemosensory effects of chemicals

Abstract: By means of these psychophysical approaches a diverse class of chemicals can be described and compared with respect to their chemosensory potency. This information can be used twofold (a) for the evaluation of existing studies reporting sensory irritations and (b) for the design of experimental exposure studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
4

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 42 publications
1
46
0
4
Order By: Relevance
“…It has been reported that higher room temperature and photochemical oxidants potentially inXuenced the formation of indoor formic acid from formaldehyde, and formic acid has a mucosal irritation eVect (Sekine et al 2001). Because such metabolized chemicals possibly inXuence SBS symptoms (van Thriel et al 2006), further studies are needed to clarify these eVects in the dwellings.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that higher room temperature and photochemical oxidants potentially inXuenced the formation of indoor formic acid from formaldehyde, and formic acid has a mucosal irritation eVect (Sekine et al 2001). Because such metabolized chemicals possibly inXuence SBS symptoms (van Thriel et al 2006), further studies are needed to clarify these eVects in the dwellings.…”
Section: Discussionmentioning
confidence: 99%
“…The three acids were selected to investigate parts of a homologous series. The chemosensory effect range of the investigated chemicals was estimated by odor and lateralization threshold as an indicator of intranasal irritation and is published elsewhere (van Thriel et al, 2006).…”
Section: Substancesmentioning
confidence: 99%
“…Im Rahmen eines Forschungsprojekts zur Abgrenzung und Differenzierung "irritativer" und "belästigender" Effekte von Gefahrstoffen [27] wurden an je 36 Män-nern und Frauen mittels statischer Olfaktometrie die Geruchschwelle und die Lateralisationsschwelle bestimmt [28,29]. Letztere bezeichnet die Konzentration, bei der Versuchspersonen in der Lage sind, bei getrennter Exposition beider Nasenlöcher anzugeben, auf welche Seite der Nase der inhalierte Stoff einwirkt.…”
Section: Toxikokinetikunclassified
“…Bei wiederholten Versuchen mit 11 bis 12 untrainierten Testpersonen wurden im selben Labor um den Faktor 3 variierende Geruchsschwellenwerte mit einem geometrischen Mittel von 2,3 mg/m 3 gefunden [42]. In einer anderen Untersuchung wurde mittels statischer Olfaktometrie eine geringfügig höhere Geruchsschwelle von 5,5 mg/m 3 ermittelt [28,29] …”
Section: Geruchswahrnehmungunclassified